Enhancement of Magnetic Field Strength and Gradient Produced by an Array of Micro-sized Parallelepiped Magnets - Tiep, Nguyen Huy; Tu, Bui Dinh; Cuong, Le Viet (VNU Journal of Science: Mathematics - Physics, 2023)
In this work, we carried out survey on magnetic field strength and gradient in space around arrays of micro-sized parallelepipedic magnets by simulation and calculation. Magnetic field distributions are a function of magnet’s size and position with respect to magnet’s surface. Our purpose is to explain how magnetic interactions evolve while dimensions of magnetic sources are reduced. Firstly, the simulations and calculations were executed for a magnet with a large surface size of 1,000×1,000 µm 2 , a thickness of 5 µm, and a residual magnetism of 1.6T perpendicular to its surface. Then, the similar works were also performed for arrays of magnets with smaller surface sizes, e.g. 1,000×500 µm 2 ; 1,000×200 µm 2 ; 1,000×100 µm 2 ; 1,000×50 µm 2 and 1,000×10 µm 2 . Consequently, both the magnetic field strength and gradient in the space which is above and near the surface of the magnets, particularly, the space from the surface of the magnets to the height of 100 µm far from the surface of the magnets, were enhanced when the magnets’ size were appropriately reduced. This suggests that the application field of the magnets will be expanded and their integration into microsystems will be grown as the size of the magnets is reduced.